Emotional intelligence and conflict management styles. Issue 3 (8th July 2019) - Chen, Helen X.; Xu, Xuemei; Phillips, Patrick
Abstract : Purpose: This paper aims to use a multi-level approach to examine the effects of emotional intelligence (EI) components on conflict management styles of Chinese managers when the respondents were in conflicts with their subordinates, peers or superiors. Design/methodology/approach: The primary research was conducted in Dalian, China, via a personal survey resulting in 885 usable observations for analysis. EI was measured using the Wong and Law Emotional Intelligence Scale (WLEIS;Wong and Law, 2002 ), which is made up of 16 questions measuring four dimensions. The conflict management component was measured via Rahim's (1983) five conflict management styles, which are avoidance, dominating, collaboration, compromise and integration. Findings: The data analyses suggested that managers at different levels possess different EI and adopt different conflict management styles when dealing with their subordinates, peers and superiors. Specifically, when subordinates were involved in a conflict, junior managers and female managers were more likely to use the dominating style, while when peers were involved in a conflict, male managers were more likely to use the dominating style. When peers were involved in a conflict, managers working in public sectors were more likely to adopt the integrating, avoiding, obliging and compromising style. The Chinese managers were found to regulate their emotions and use of their emotions effectively in conflict with their peers and supervisors and thus they tended to adopt the avoiding, integrating and obliging style. Self-emotions appraisal and others emotions appraisal were significant to the adoption of the obliging style to handle conflict with their peers and supervisors. Use of emotions effectively was significant for the Chinese managers adopting the compromising style in conflicts with their peers, superiors and subordinates. Research limitations/implications: The authors could only reach employees working and living in one city, which affects the generalizability of the paper. Practical implications: Training should be provided to managers at different levels on the awareness of the impact of EI on conflict management at workplace. Originality/value: There is little existing research on how employees across different levels within organisations in China moderate their EI according to the party they are interacting with. The objective of this paper is to stimulate further debate on the matter, thereby improving the understanding of EI moderation.